Exploring the relationship between Iso 14001 Ems and Esg performance of Malaysian companies - Sia, Mal Kong; Yew, Wong Chin; Tan, Say Keat; Ong, Daniel Zhang Jie; Sia, Wen Di (Penerbit Universiti Kebangsaan Malaysia, 2024)
Global environmental concerns have garnered significant attention in recent times. Concerns about encouraging more ecologically friendly production to lessen the effects of pollution have been raised by industrial operations that cause environmental pollution. The adoption of an environmental management system in Malaysian firms, however, has received little attention. This paper explores the mediating effect of Environmental, Social and Governance (ESG) framework on the relationship between ISO 14001 Environmental Management System (EMS) and ESG performance of Malaysian companies. Partial Least Squares Structural Equation Modeling (PLS-SEM) using SmartPLS 4 was employed to assess the relationship through a conceptual model developed for this purpose. A total of 86 completed responses were collected from the targeted respondents in Malaysia of different industries. With ESG framework as a mediator, ISO 14001 EMS has an insignificant relationship with ESG performance, and the R2 value of ESG performance is 0.243. When the ESG framework is removed, ISO 14001 EMS has a significant relationship with ESG performance, and the f-square value is 0.176. This effect size is considered medium. The results provide an empirical proof for Malaysian companies to adopt the ISO 14001 EMS as a business tool, with ESG framework as a mediator in order to enhance their ESG performance. The study’s conclusions highlight the implications of using ISO 14001 EMS as a tool for businesses in Malaysia to improve ESG performance.